Pelatihan Origami bagi Guru-Guru PAUD Untuk Meningkatkan Profesionalisme Guru - Zaenab Munqidzah; Liastuti Ustianingsih (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
Creativity is an important aspect for every child, especially for kindergarten children. The level of creativity of the children both in school and home will have an effect on their learning achievement. There for, children creativity should be developed and facilitated with various facilities and infrastructure. One of the way to develop children's creativity is the skills of paper folding (origami). The lack of children's creativity, especially in the art of origami skills, is influenced by some factors such as the lack of creativity of the children itself, the facilities and infrastructures, unsupportive environment, the possibility of unprofessional teachers in applying the basic skills of teaching, either skills using variations or style of teaching methods. By improving the professionalism of the teachers, it can be expected to create a fun learning-teaching process for learners